VERBALIZATION OF THE CONCEPT AMERICAN DREAM IN THE PLAY “ANNA CHRISTIE” BY EUGENE O’NEILL - Marchuk, Т. L.; Stekhnovych, М. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article analyzes contemporary linguistic and literary approaches to the interpretation of the term concept. The artistic concept as a symbiosis of individual-author’s reflections and elements of the national picture of the world is illuminated. The peculiarities of the author’s interpretation of the concept AMERICAN DREAM are traced on the material of the play “Anna Christie” by Eu. O’Neill. It is proved that the implementation of the concept occurs through the verbal expression of the emotions and feelings of the heroes as semantic markers.